(untitled) (Journal of Industrial and Mechanical Engineering, 2021)
The industry dedicated to the manufacture of materials for brake applications has produced a new series of materials that have a great extension of the useful life without losing their shape and properties. In this sense, to evaluate these advantages, the effect of contact pressure on wear resistance, friction and temperature of a new material designed for braking applications was studied. The tribological system consisted of a pin of gray cast iron and a disk of the material under study. The load applied was 10 N and the rotational speed of the disk was 480 rpm. The pin with flat surface presented the lowest contact pressure. The friction coefficient was calculated by means of the measurement of the tangential force with a type S load cell. The temperature was obtained with a K thermocouple at 1 mm from the contact surface. Weight loss was measured and the damaged surface was characterized. It was observed that in the initial period the friction coefficient was lower for the samples tested with flat pin and no great differences were observed in the stable period in both conditions. The temperature was 70 to 90 ° C. The samples tested with a flat pin showed a homogeneous wear surface of wide 6 mm, while the specimens with a hemispherical pin showed an increase in the wear track to 2 mm.